Cervical cancer in the Autonomous Province of Vojvodina, Serbia, 2016-2021 - Ljubičić, Stefan; Štrbac, Mirjana; Nikolić, Nataša; Šušnjević, Sonja; Dugandžija, Tihomir; Petrović, Vladimir; Ristić, Mioljub (Archive of Oncology, 2024)
Background: Cervical cancer is a major global health problem, and one of the most common causes of cancer in women. This descriptive epidemiological study aimed to provide an overview of the cervical cancer incidence and mortality in Vojvodina. Methods: The data from the Serbian Cancer Registry regarding the cervical cancer incidence and mortality for the period 2016–2021 were analyzed. Results: During the observed 6-year period, the average age-standardized incidence rates of cervical cancer in Vojvodina and Serbia were 20.4 and 19.1 per 100,000 women, respectively. The average age-standardized incidence rates by the district of Vojvodina ranged from 16.8 to 30.2/100,000. The average age-standardized cervical cancer mortality rate in Vojvodina and Serbia was 7.0 and 6.6/100,000, respectively. The average mortality rates by the district of Vojvodina ranged between 5.6/100,000 and 9.9/100,000. Conclusion: The cervical cancer incidence and mortality rates in Vojvodina exhibited significant variation across different districts and observed years, with their average values surpassing the national average. To improve the epidemiological situation of cervical cancer in Vojvodina, it is imperative to enhance the implementation of organized screening at the district level, coupled with intensified efforts to promote HPV vaccination throughout Vojvodina. Additionally, more research on screening coverage and vaccination rates and improved reporting cervical cancer cases and deaths are needed.
Keywords: Uterine Cervical Neoplasms; Epidemiology; Incidence; Mortality; Papillomavirus Vaccines; Serbia